Urbanism in the City of Salé: its Patterns and Factors - Arabi, Nezha; Aneflouss, Mohamed (Journal of Humanities & Social Sciences, 2024)
The city of Salé is among the largest urban polers in Morocco, undergoing significant transformations at the socioeconomic and urbanistic levels, which poses several challenges to urban planning strategies.Therefore, this study aims to answer a key problem centered around monitoring the prevailing urban patterns in the urban councils of the city of Salé and highlighting the controlling factors. To address the issue, we relied on the descriptive approach, analytical method, and statistical data that were used in conducting the research on the level of population demographics, unemployment indicators, poverty, and vulnerability. In addition, we worked on processing the spatial visualization of the (SASPlanet) program to obtain maps showing urban patterns and components of the urban fabric of the city, using Geographic Information Systems (SIG).  Thus, the result showed that what the urban area of the city of Salé is characterized by two dominant patterns of urbanism, legal urbanism and illegal urbanism, which includes informal housing and shantytowns that distinguish the city’s urbanism, indicating a lack of control over the general trend of urbanism by monitoring devices, ultimately resulting in a city with a varied morphology, with legal and illegal residential clusters that continue to define the urban landscape until the year 2024. The study concluded that the city of Salé is classified among the major cities in Morocco in terms of demographic growth and urban expansion, which has resulted in a diverse urban fabric, A variety of mechanisms have contributed to consolidating and establishing this characteristic, making it the distinctive feature of the entire urban area. Thus, urbanism in the city of Salé is characterized by its spontaneity and informality without prior planning at a rate of 12.09%, which limits the effectiveness of urban development programs and measures.
Keywords: Salé city; patterns of urbanism; urban fabric; informal housing; shanty towns